2019
DOI: 10.1055/a-1041-4305
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound for Early Prediction of Response of Breast Cancer to Neoadjuvant Chemotherapy

Abstract: Purpose To evaluate the time-intensity curve (TIC) parameters on contrast-enhanced ultrasound (CEUS) for early prediction of the response of breast cancer to neoadjuvant chemotherapy (NAC). Materials and Methods This prospective study included 41 patients with breast cancer. CEUS was performed before and after the first cycle of NAC. TIC parameters were analyzed for different regions of interest (ROIs). ROI 1 targeted the hotspot area of greatest enhancement, ROI 2 delineated the area of hyperenhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…A combination of CEUS parameters and molecular subtype (model 2) exhibited a good performance (AUC =0.841) in the prediction of a good response when compared to a combination of the conventional US and molecular subtype (model 1). Studies have documented that CEUS parameters can be used to predict responses to NAC (17,21,23,24). Lee et al (21) reported that, in breast cancer, mTT changes were correlated with responses to NAC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A combination of CEUS parameters and molecular subtype (model 2) exhibited a good performance (AUC =0.841) in the prediction of a good response when compared to a combination of the conventional US and molecular subtype (model 1). Studies have documented that CEUS parameters can be used to predict responses to NAC (17,21,23,24). Lee et al (21) reported that, in breast cancer, mTT changes were correlated with responses to NAC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have documented that CEUS parameters can be used to predict responses to NAC (17,21,23,24). Lee et al (21) reported that, in breast cancer, mTT changes were correlated with responses to NAC. In addition, RT has been shown to have a fair predictive value for responses during treatment (AUC =0.710) (23).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations